2014
DOI: 10.1063/1.4892823
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electric field concentration using nanopeak structures on the current–voltage characteristics of resistive switching memory

Abstract: An attempt to reduce the SET voltage and RESET current of resistive switching (RS) memory was made using a geometric array of nanopeak (NP) structures. Bottoms of anodic porous alumina were used to form the NP structures that act as guides for the formation of conductive filaments that effectively concentrate the electric field. Samples were fabricated with flat surfaces (FS) and with two types of NP structure with different NP pitch. The NP samples provided SET voltages less than 2 V with narrow distributions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…[23][24][25][26][27][28][29] In the case of anodizing of metallic alloys, resulting oxide will be a mixed oxide in which the atomic ratio between partner metals can be different with respect to the underlying alloys depending on transport numbers of involved cations. To date, there are several papers in which porous anodic aluminum oxide is used as a matrix for the fabrication of ReRAMs [30][31][32][33] or anodic nanostructured oxides are used as solid electrolytes, [34][35][36][37][38] but only few papers discuss on ReRAMs devices with barriertype anodic oxides however not showing some particular promises. [39][40][41][42] Here we demonstrate Ta/Ta 2 O 5 /Pt system with electrochemically grown Ta Increasing the voltage over + 3 V leads to a formation of filament i.e.…”
mentioning
confidence: 99%
“…[23][24][25][26][27][28][29] In the case of anodizing of metallic alloys, resulting oxide will be a mixed oxide in which the atomic ratio between partner metals can be different with respect to the underlying alloys depending on transport numbers of involved cations. To date, there are several papers in which porous anodic aluminum oxide is used as a matrix for the fabrication of ReRAMs [30][31][32][33] or anodic nanostructured oxides are used as solid electrolytes, [34][35][36][37][38] but only few papers discuss on ReRAMs devices with barriertype anodic oxides however not showing some particular promises. [39][40][41][42] Here we demonstrate Ta/Ta 2 O 5 /Pt system with electrochemically grown Ta Increasing the voltage over + 3 V leads to a formation of filament i.e.…”
mentioning
confidence: 99%
“…The major advantages of the localized electric field enhancement by NCs can be utilized to design the bottom electrode layer. Several nanostructures-based bottom electrodes are reported to improve the performance of RRAM devices, such as nano-pyramid [123], nano-peak [124], arc-shaped [125], and so on [126]. A detailed review on defect engineering in RRAM is reported in Reference [127].…”
Section: Defect Engineering Of Resistive Memory Devicesmentioning
confidence: 99%
“…2(b) and (c). The edges of the needle architectures possess positive charges by the principle of electric field concentration; 19 thus, the negatively charged GO was accumulated on the AuNS layers by electrostatic interactions. Indeed, the distribution of elements in the energy dispersive X-ray (EDX)-mapping (Fig.…”
mentioning
confidence: 99%